DIGITAL ECONOMY: DEVELOPMENTS IN UZBEKISTAN AND WORLD PRACTICE (Marketing Journal, 2024)
This article studies and analyzes digitalization, its important aspects of the digital economy today, and the advantages of digitalization in providing services to the public. The impact of digital transformation on the financial services market is also considered. Reviewed research related to digital transformation of financial services. The article examines the experience of South Korea, which is a world leader in the field of digitalization. The existing digital systems and Internet portals in our country were also analyzed.